2018
DOI: 10.1007/s00432-018-2586-8
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation-associated miRNAs-494, -205, -21 and -126 detected by in situ hybridization: expression and prognostic potential in breast carcinoma patients

Abstract: The present paper reports for the first time on the prognostic value of miRNA-494 in invasive breast cancer. Particularly, detection of miRNA-494 could benefit patients with node-negative breast cancer in identifying subgroups with aggressive disease. Based on our experience, the developed automatic ISH method to visualize altered levels of miRNAs-494, -205, -21 and -126 could be applied to routine pathology diagnostics providing that conditions of tissue treatment, especially fixation delays, are managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In the past decades, miRNAs have been intensively studied in primary breast tumor tissue leading to the identification of a number of diagnostic and prognostic miRNA signatures (23)(24)(25). Altered expression of several miRNAs, such as miR-7, miR-10a, miR-21, miR-126, miR-128, miR-205, miR-210, miR-484, miR-489, miR-494, and miR-548 have been reported in breast cancer (26)(27)(28). As minimally invasive disease biomarkers, our recent study have identified 18 diagnostic circulatory miRNA panel in breast cancer patients (22).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, miRNAs have been intensively studied in primary breast tumor tissue leading to the identification of a number of diagnostic and prognostic miRNA signatures (23)(24)(25). Altered expression of several miRNAs, such as miR-7, miR-10a, miR-21, miR-126, miR-128, miR-205, miR-210, miR-484, miR-489, miR-494, and miR-548 have been reported in breast cancer (26)(27)(28). As minimally invasive disease biomarkers, our recent study have identified 18 diagnostic circulatory miRNA panel in breast cancer patients (22).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs directly bind with target genes and regulate their expression, thereby altering proliferation, 24 , 25 migration 26 and invasion of cells. 27 HIF1α is key member of the hypoxia-inducible factors family that regulates cellular response to hypoxia.…”
Section: Discussionmentioning
confidence: 99%